Kemampuan Dribbling Murid SDN 58 Tanete Bulukumba Ditinjau Dari Tinggi Badan, Panjang Tungkai Dan Panjang Lengan - Suwardi, Suwardi (SPORTIVE: Journal Of Physical Education, Sport and Recreation, 2025)
This study aimed to: (1) describe the level of dribbling ability among students at SDN 58 Tanete Bulukumba; (2) analyze the relationship between height and dribbling ability; (3) analyze the relationship between leg length and dribbling ability; (4) analyze the relationship between arm length and dribbling ability; and (5) analyze the simultaneous relationship between height, leg length, and arm length with dribbling ability among students at SDN 58 Tanete Bulukumba. This study employed a quantitative approach with a correlational design. The research sample consisted of 48 fourth and fifth-grade students selected using purposive sampling technique. Data were collected through anthropometric measurements using a stadiometer and anthropometric tape measure, as well as dribbling ability tests using a modified AAHPERD test. Data analysis utilized descriptive statistics, Pearson correlation, and multiple linear regression with IBM SPSS Statistics version 26. The results showed that: (1) students' dribbling ability was at varying levels with the majority (37.5%) in the moderate category and an average completion time of 18.45 seconds (SD = 2.87); (2) there was a strong and significant negative relationship between height and dribbling ability (r = -0.692, p < 0.05) with a contribution of 47.9%; (3) there was a strong and significant negative relationship between leg length and dribbling ability (r = -0.674, p < 0.05) with a contribution of 45.4%; (4) there was a strong and significant negative relationship between arm length and dribbling ability (r = -0.637, p < 0.05) with a contribution of 40.6%; and (5) simultaneously, all three anthropometric variables had a significant relationship with dribbling ability (F = 21.048, p < 0.05) with R² = 0.590, although only height was significant in partial analysis (β = -0.425, p = 0.004). The conclusion of this study is that anthropometric characteristics, particularly height, have a strong relationship with dribbling ability in elementary school students, with a combined contribution of 59%.